High vapor pressure deficit drives salt‐stress‐induced rice yield losses in India. (8th January 2015) - Tack, Jesse; Singh, Rakesh K.; Nalley, Lawton L.; Viraktamath, Basavaraj C.; Krishnamurthy, Saraswathipura L.; Lyman, Nate; Jagadish, Krishna S. V.
Abstract Flooded rice is grown across wide geographic boundaries from as far north as Manchuria and as far south as Uruguay and New South Wales, primarily because of its adaptability across diverse agronomic and climatic conditions. Salt‐stress damage, a common occurrence in delta and coastal rice production zones, could be heightened by the interactions between high temperature and relative humidity (vapor pressure deficit – VPD). Using temporal and spatial observations spanning 107 seasons and 19 rice‐growing locations throughout India with varying electrical conductivity (EC), including coastal saline, inland saline, and alkaline soils, we quantified the proportion of VPD inducing salinity damage in rice. While controlling for time‐invariant factors such as trial locations, rice cultivars, and soil types, our regression analysis indicates that EC has a nonlinear detrimental effect on paddy rice yield. Our estimates suggest these yield reductions become larger at higher VPD. A one standard deviation (SD) increase in EC from its mean value is associated with 1.68% and 4.13% yield reductions at median and maximum observed VPD levels, respectively. Yield reductions increase roughly sixfold when the one SD increase is taken from the 75th percentile of EC. In combination, high EC and VPD generate near catastrophic crop loss as predicted yield approaches zero. If higher VPD levels driven by global warming materialize in conjunction with rising sea levels or salinity incursion in groundwater, this interaction becomes an important and necessary predictor of expected yield losses and global food security.